ISSUES OF ENLIGHTENMENT IN THE ACTIVITIES OF THE JADIDS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article provides information about the activities of the Jadids and their views on the education of a harmoniously developed generation.